2005
DOI: 10.1108/02686900510598849
|View full text |Cite
|
Sign up to set email alerts
|

Conversations with internal auditors

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 21 publications
4
56
0
2
Order By: Relevance
“…Being subordinated to external auditing, Danish IA draws on the professional status of external auditing in a way similar to that reported by Van Peursem (2004, 2005 in New Zealand. Abbott (1988) notes that subordination to an established profession followed by subsequent differentiation of the jurisdiction is a common long-term strategy of professionalization.…”
Section: Discussionmentioning
confidence: 96%
“…Being subordinated to external auditing, Danish IA draws on the professional status of external auditing in a way similar to that reported by Van Peursem (2004, 2005 in New Zealand. Abbott (1988) notes that subordination to an established profession followed by subsequent differentiation of the jurisdiction is a common long-term strategy of professionalization.…”
Section: Discussionmentioning
confidence: 96%
“…Van Peursem (2005), based on interviews with Australian internal auditors, concluded that independence from management is a dominant feature of successful auditing programs. Those auditors able to set their own agenda seem to be the most powerful in this respect because their selection of what to audit and when they can include assessments of senior managers as well as assessments for them.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The subject is worthy of attention because internal auditors are important, even crucial, in an economy that relies upon independently produced information (Van Peursem 2005). Indeed, IA has become an indispensable management tool for achieving effective control in both public and private organisations (Eden and Moriah 1996).…”
mentioning
confidence: 99%
“…The auditors' competencies can also increase the effectiveness of the IA team by improving the recognition of their role within the organization. Previous studies underlined that line managers often believe that internal auditors do not have enough knowledge to provide useful help (Griffiths, 1999; Van Peursem, 2004, 2005) and, if this is the case, they do not take into account their advice, hence reducing the effectiveness of IA (Van Peursem, 2004, 2005).…”
Section: Formulating the Hypothesesmentioning
confidence: 99%